Desenvolvimento e avaliação clínica de um gel facial de própolis vermelha na terapêutica da acne vulgar de grau 1 e 2 - Mormino, Karla Bruna Nogueira Torres (2020)
Introduction: Acne is a chronic, multifactorial and universal condition that usually appears in adolescence and can extend into adulthood, affecting both genders. For acne treatment, topical products are widely used, whether or not associated with systemic medication. Keratolytic agents, benzoyl peroxide and antibiotics are often used. Antibiotic therapy against Propionibacterium acnes (P.acnes) is the standard, however, due to the adverse effects and bacterial resistance related to the use of synthetic antibiotics, there is currently a tendency to seek alternative product treatments where the active principles of natural products are being increasingly exploited, as in the case of propolis. Objectives: This study aimed to conduct a prospective study of propologic dermatological patents; to develop, evaluate in vitro and in vivo the effectiveness of a facial gel from the hydroalcoholic extract of Brazilian red propolis (BRP), in the treatment of acne vulgaris, grade 1 and 2. Material and methods: Initially a documentary study of patents in intellectual property banks in Brazil and worldwide. The second stage was divided into identification and characterization of acquired propolis, strain activation and in vitro microbiological study. The third step performed stability tests on the gel. Carbopol 940® and Natrosol® polymers were used to identify the best formulation possible. These formulations were stored in a greenhouse at room temperature (27.5 ± 2.5 ° C) and analyzed immediately after preparation, as well as after 30 and 60 days of storage. The studies started with pH tests and the weight of the formulations. The obtained data were used to evaluate the organoleptic and physicochemical characteristics. The last stage of the research is a randomized, double-blind, longitudinal controlled clinical trial study. The study was conducted at the Laboratory of Manipulation and Quality of Pharmacy School and Microbiology of the Catholic University Center of Quixada, where 60 participants were selected, divided into two groups: BRP gel and benzoyl peroxide, for microbiological comparison before and after the different treatments. Results: WIPO was the bank with the largest number of deposits (43.7%), while INPI found only three deposits (2.9%). The number of patent filings has increased over the years, especially after 2014, mainly from China (40.8%), the United States (29.1%) and South Korea (20.4%). As for the type of product, there were mainly creams and masks, but most documents did not have product specifications. All strains in this study were sensitive, with MIC90 ≤ 2.5%. Regarding the organoleptic characteristics of the formulation with Carbopol 940® 0.5% it was observed intense yellow color, characteristic odor, firm uniform gelatinous appearance, more fluid than 1%. In the formulation with Carbopol 940® 1% the color displayed was citrus yellow, characteristic odor and uniform appearance, like jelly. In the formulation of Natrosol® 0.5% honey yellow color, intense characteristic odor, biphasic appearance, fluid gel type, with low amount of foam. In Natrosol® 1% was the caramel yellow color, with intense characteristic odor and biphasic appearance, fluid gel type and abundant foam. It was observed that there was a decrease in mass in all polymers. In addition, fungal colonies were seen in Natrosol® formulations, especially in 0.5%. In the in vivo study, it was observed that 90 days after initiation, both treatments, propolis 2.5% gel (p = 0.0107) and benzoyl peroxide 5% gel (p <0.0001) showed a significant reduction in the counted units when compared to baseline. In the intergroup comparison there was significance (p = 0.0403) of the group treated with benzoyl peroxide 5% when compared to propolis 2.5%.Conclusion: For centuries, the pharmacological properties of propolis have been documented in the literature. It is an interesting product to be incorporated into materials, including those for dermatological use, such as gels. In this study, the results showed that gels manipulated with Natrosol® showed fungal colonies with greater evidence at 0.5% concentration and Carbopol 940® 1% gel was the most stable formulation. In the studies performed, in vitro antimicrobial activity and in vivo clinical efficacy on P. acnes were confirmed. It is concluded that propolis gel is a strong option in acne therapy, as it is an innovative product of natural origin, with proven effectiveness.